Antifungal effect of Algerian essential oil nanoemulsions to control Penicillium digitatum and Penicillium expansum in Thomson Navel oranges (Citrus sinensis L. Osbeck) - Gharzouli, Merihane; Aouf, Abdelhakim; Mahmoud, Engy; Ali, Hatem; Alsulami, Tawfiq; Badr, Ahmed Noah; Ban, Zhaojun; Farouk, Amr (Frontiers in Plant Science, 2024)
Fungal infection is a potential issue in citrus fruits, while essential oils such as Cymbopogon citratus and Citrus limon could be better alternatives to synthetic fungicides in orange preservation. The nanoparticles produced during ultrasonication exhibited a monomodal distribution of particle sizes with a mean zeta potential and a polydispersity index mean value was 74.12 nm, -38.4 mV, and 0.19 for C. citratus and 103 nm, -28.4 mV, and 0.22 for C. limon. The micrographs of the nanoemulsions exhibited spherical morphology with diverse nanometer-scale sizes. Nano emulsification enhances the levels of neral and geranial in both oils while reducing the levels of limonene, γ-terpinene, and β-myrcene. The essential oils and their nanoemulsions exhibited good MIC values against Gram-positive and Gram-negative bacteria, ranging from 2% to 0.12%, while MBC was 4% to 0.25% (v/v) for both. The extended genetic investigation of the isolated fungal strains from Thomson Navel oranges through analysis of the ITS sequences and BLAST indicated 100% homology to those of Penicillium digitatum and Penicillium expansum. Both oils' MIC and MFC values and nanoemulsions ranged from 0.12% to 0.06% and 2% to 0.03% against P. expansum and P. digitatum, respectively. Applying nanoemulsified C. limon and C. citratus as a coating on orange fruits significantly reduced the spread of P. expansum and P. digitatum fungi compared to the control. Coating with nanoemulsions reduced the negative changes in quality parameters during storage, such as weight loss, firmness, TSS, TA, pH, and ascorbic acid content. C. limon nanoemulsion did not alter the coated fruits' sensory attributes compared to C. citratus nanoemulsion.